(untitled) (Experimental biology, 2015)
In work the regular analysis is carried out and is determined on seasonal taxonomy specific structure and seasonal dynamics of algoflors of lakes (Kopa, Burabai, Zerenda ) in Kokshetau region. If to give a complex estimation specific structure algosenoz and results of biotesting and carried out hydrochemical, microbiological researches, is established, that waters of lake Коpа concern to 5 class of a level of pollution; waters of lakes Burabai and Zerenda concern to 3 class of a level of pollution.